1990
DOI: 10.1002/nau.1930090602
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic changes in women using diaphragms

Abstract: Although the diagphragm is widely used as a method of contraception, little is known as to its effect on urethrovesical function. To evaluate whether the diaphragm, or diaphragm size, influences bladder function, urodynamic studies were performed in nine nulliparous volunteers. Maximum and mean flow rates were significantly decreased with diagphragm use (P<0.02). Urethral resistance was significantly increased with both diaphragm sizes compared to control values (P<0.02). There were no significant changes in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The possible change in urodynamic voiding parameters after vaginal pessary placement is still controversial. The usage of the standard contraceptive diaphragm was reported to compress the vesicourethral angle and caused an increase in maximal urethral closer pressures 15 and voiding detrusor pressure 16 . Ghoniem et al 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible change in urodynamic voiding parameters after vaginal pessary placement is still controversial. The usage of the standard contraceptive diaphragm was reported to compress the vesicourethral angle and caused an increase in maximal urethral closer pressures 15 and voiding detrusor pressure 16 . Ghoniem et al 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The usage of the standard contraceptive diaphragm was reported to compress the vesicourethral angle and caused an increase in maximal urethral closer pressures 15 and voiding detrusor pressure. 16 Ghoniem et al 13 recommended gauze packing as it will not change other urodynamic parameters beside its simple usage. However, a more recent study by Chaikin et al 17 on continent women with severe urogenital prolapse reported that there was no increase in detrusor pressure and no patients without obstruction had bladder outlet obstruction after vaginal pessary placement.…”
Section: Discussionmentioning
confidence: 99%